Burden of COVID‐19 disease in Kurdistan province in west of Iran using disability‐adjusted life years. Issue 3 (22nd March 2023) - Alinia, Cyrus; Bolbanabad, Amjad M.; Moradi, Ghobad; Shokri, Azad; Ghaderi, Ebrahim; Adabi, Jalil; Rezaei, Satar; Piroozi, Bakhtiar
Abstract: Background and Aims: During the coronavirus disease 2019 (COVID‐19) pandemic, about seven million people were infected with the disease, of which more than 133, 000 died. Health policymakers need to know the extent and magnitude of the disease burden to decide on how much to allocate resources for disease control. The results of this investigation could be helpful in this field. Methods: We used the secondary data released by the Kurdistan University of Medical Sciences between February 2020 to October 2021 to estimate the age‐sex standardized disability‐adjusted life years (DALY) by the sum of the years of life lived with disability (YLD) and the years of life lost (YLL). We also applied the local and specific values of the disease utility in the calculations. Results: The total DALY was estimated at 23316.5 and 1385.5 per 100, 000 populations The YLD and YLL constituted 1% and 99% of the total DALY, respectively. The DALY per 100, 000 populations was highest in the men and people aged more than 65 years, but the prevalence was the highest in people under the age of 40. Conclusions: Compared to the findings of the "burden of disease study 2019, " the burden of COVID‐19 in Iran is ranked first and eighth among communicable and noncommunicable diseases, respectively. Although the disease affects all groups, the elderly suffer the most from it. Given the very high YLL of COVID‐19, the best strategy to reduce the burden of COVID‐19 in subsequent waves should be to focus on preventing infection in the elderly population and reducing mortality.